Gender dimensions of Viet Nam's comprehensive macroeconomic and structural reform policies - Le Anh Tu Packard (United Nations Research Institute for Social Development (UNRISD), 2006)
From a gender perspective, Viet Nam is an interesting case study because it is widely seen as a 'globalization' success story where historically the social and political status of women have been high compared with women's status in many other developing countries. At the same time, there is concern that women's status may be eroding during the country's rapid transition to a market economy. Thus, it is of interest to examine the relationship between gender equality and economic performance, and to assess how women have fared when macroeconomic and structural reforms are judged to have produced successful results for the society as a whole. Viet Nam's recent reform experience is particularly instructive because it helps to identify the preconditions for women to benefit from these reforms. Similar to other rapidly growing Asian countries, Viet Nam's high growth has been accompanied by increased gender inequality as well as increased income inequality. Policy makers are paying more attention to this phenomenon of growing inequality because the country is entering a new development phase which involves an acceleration of the globalization process. At risk are poor households (many headed by single mothers) in rural and remote areas which are least able to cope with the transmission of external shocks. This paper seeks to contribute to a better understanding of macroeconomic policies that benefit women by analysing the links between reform, gender equality, economic development and women's welfare as they played out in Viet Nam during the 1990s, when the government carried out far-reaching and comprehensive reforms. It employs descriptive, narrative and quantitative approaches to explain how macroeconomic and market liberalization policies, although gender-neutral in intent, can give rise to gendered outcomes as a result of various underlying and interrelated factors. These include social attitudes and conventions influenced by patriarchal values, the pattern and structure of occupational segregation and related gender wage differentials, gender differences in education levels, and labour regulations that have the effect of increasing productivity differences between men and women. The main finding of this paper is that the welfare of women in Viet Nam generally improved as a result of macroeconomic stabilization and controlled external liberalization policies adopted by a government that espoused a 'developmentalist state' model...
Keywords: 330